Yield and Storability of Onion (Allium cepa L.) Ecotypes as Influenced by Irrigation Intervals in Sudan Savanna of Nigeria - M, Muhammad A.; Na-Allah, M. S; A, Muhammad; U, Mohammed I.; A, Musa; Adigari, J. J; J, Yusuf I. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Field trials were conducted simultaneously during the 2023/2024 dry seasons at the Kebbi State University of Science and Technology, Aliero University orchard located at Aliero and The second experiment were conducted at Usmanu Danfodio University Sokoto Teaching and research Fadama farm. The area is located at Sokoto State, both locations are in Sudan Savannah agro-ecological zone of Nigeria. The aim was to study the effects of irrigation interval on yield and the storability of twelve onion ecotypes (Allium cepa L.). Treatments consisted of three irrigation intervals (3, 6 and 9 days), and twelve onion ecotypes (Ex-Dikwa, Ex-Kaffe, Ex-Bama, Ex-Alieru, Ex-Gothege, Ex-Gada, Ex-Wurno, Ex-GHM, Ex-Gaya, Ex-Borno, Ex-Lahodu, and Ex-Goronyo). Factorial combinations of irrigation intervals were allocated to the main-plots, while ecotypes were assigned to the sub-plots in a randomized completely block design, replicated three times. The size of each sub-plot was 1x2m (4m2). Result revealed that plant height, number of leaves, above ground biomass, total biomass,fresh bulb weight, cured bulb diameter and bulb diameter were higher with 3 to 6 days irrigation interval, while weight loose and weight loose in (%) were higher in 3 days irrigation interval. Higher percentage of rotted bulbs and sprouting were recorded by frequent irrigation of 3 days interval. Plant height, number of leaves especially at early growth stages, and number of leaves throughout the crop cycle were higher at 3 days irrigation, eoctypes Ex-Kaffe and Ex-Dikwa has the highest plant height and leave number at 4, 8 and 12 WAT in the both locations, also total biomass, above ground biomass, fresh bulb weight recorded the highest weight value followed by Ex-Dikwa. Similarly, 3 days irrigated ecotypes has the highest weight value followed by 6 days irrigation interval while 9 days irrigation ecotypes recorded the least weight value. Ex-Borno, Ex-Dikwa and Ex-Kaffe recorded the highest weight value after undergoing curing period in the two locations, while ExGHM, Ex-Lohodu has the least weight value. Likewise in sokoto Ex-Dikwa and Ex-Kaffe has the highest weight value. In terms of bulb diameter (cm) Ex-Dikwa recorded the highest value in Aliero while the least was recorded in Ex-Goronyo, similarly in Sokoto Ex-Dikwa, Ex-Kaffe and Ex-Borno has the highest weight values after curing while Ex-Aliero, Ex-Gothege, Ex-Gada, Ex-GHM, Ex-Lohodu and Ex-Goronyo followed. In terms of weight loose, Ex-Borno loses weight drastically for the whole of the storage period followed by Ex-Gaya and Ex-Goronyo. Equally, Ex-Wurno and Ex-Kaffe recorded less weight loose during the storage period. Based on the result of this study, 3 days irrigation scheduling proved the best for more number of leaves plant height and fresh bulb yield in the study area, ecotypes Ex-Dikwa and Ex-Kaffe could be adopted due to its potential for higher yielding, while 9 days irrigation interval is the best for post-harvest storage and Ex-Goronyo were found superior.